EVALUASI DAMPAK PENERAPAN AUTOMATED DISPENSING MACHINE TERHADAP DISPENSING ERROR DI FARMASI RAWAT JALAN INSTALASI FARMASI RUMAH SAKIT BETHESDA YOGYKARTA - Purwoadi Sujatno; Rizaldy Taslim Pinzon; Andreasta Meliala (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2016)
Dispensing error is not uncommon in the medication proccess. Otomatisation of outpatient pharmacy services decrease the incidence of dispensing error, as well as improving the efficiency of picking, packing and labeling process. Since August 2014 an automated dispensing machine was installed in outpatient pharmascy Bethesda Hospital Yogyakarta, integrated with electronic prescribing and hospital information system. The objective of the study was to evaluate the impact of automated dispensing machine on the dispensing error at outpatient pharmacy Services using before and after study method. The procentage of drugs deliver by automated dispensing machine at the third and sixth month of implementation was 46% and 59%. Failure mode and effeect analysis of dispensing process done before the implementation, and the integration with electronic prescription and hospital information system, as well as the development of smart pack is the key of successed. The average of medications picked after the implementation of automated dispensing machine was (37,915.33 3,160.12), higher than before implementation (36,812.67 2,890.81), but not significant. The average of dispensing error after implementation (15,67 6,28) was reduced significantly (p0,05) than before (50.33 34.47). The most frequent type of dispensing error were wrong quantity dispensed, wrong drug dispensed and wrong strength dispensed. The implementation of automated dispensing machine significantly reduce the incidence of dispensing error. Further investigaation needed to know the incidence of dispesning error cause by the machine and manual and factors that influenced.